'Arms for mobility': policing partnerships and material exchanges in Nairobi, Kenya. (7th February 2020) - Diphoorn, Tessa
ABSTRACT: This paper analyses two policing arrangements between the state police and several private security companies in Nairobi, Kenya. These arrangements entail that police officers team up together with security officers in their company vehicles. As private security officers are unarmed in Kenya by law, there is a direct exchange of ' arms for mobility ', an emic term that refers to an exchange of firearms for 'mobility', i.e. vehicles and other financial resources. Based on ethnographic fieldwork on policing in Nairobi, Kenya between 2014 and 2018, I analyse how this exchange (re)centralises the state police and the critical role of the 'arms' in this process. Drawing from Star and Griesemer (1989), I see the firearm as a 'boundary object' that brings policing actors together, but simultaneously reaccentuates their differences and in this case, reaffirms and repositions the dominant role of the state police in the Kenyan policing landscape. With this argument, I aim to further prompt more in-depth studies on how certain objects define policing practices, and emphasise the merit of ethnographic research as a methodological approach to uncover such dimensions.